Fourth Czechoslovakian Symposium on Combinatorics, Graphs, and Complexity - Nesetril, Jaroslav; Fiedler, Miroslav (Annals of discrete mathematics, 1992)
This volume in the Annals of Discrete Mathematics brings together contributions by renowned researchers in combinatorics, graphs and complexity. The conference on which this book is based was the fourth in a series which began in 1963, which was the first time specialists from East and West were able to come together. The 1990 meeting attracted 170 mathematicians and computer scientists from around the world, so this book represents an international, detailed view of recent research.